Analisis Tindakan Pencegahan Strok pada Penderita Hipertensi - Erna Sariana; Nur Achirda; Dwi Agustina; Iswahyudi Iswahyudi (Faletehan Health Journal, 2025)
One of the non-communicable diseases that has become a major health problem in Indonesia is hypertension which can lead to dangerous complications such as stroke. Stroke patients often experience death and may also suffer from disability, so the preventions are urgently required. The purpose of this study was to identify stroke prevention practices among patients with hypertension. This research employed a cross-sectional design with a sample of 107 hypertension patients visiting the Cipayung Health Centre. The study was conducted from May to September 2024. Data were collected using a questionnaire and analysed through univariate, bivariate (chi-square test), and multivariate (logistic regression test) analysis. Based on the research findings, most respondents had good stroke prevention practices (70.1%). The variables that showed a significant association with stroke prevention practices were education (p=0.049; OR=2.603), knowledge (p=0.0001; OR=16.611), sources of information (p=0.033; OR=5.455), family support (p=0.001; OR=5.455), and support from health workers (p=0.047; OR=2.737). Age (p=0.813), gender (p=0.720), and attitude (p=0.115) were not statistically associated. The dominant factor was knowledge (OR=14.788), meaning that hypertensive patients with high knowledge were 14.788 times more likely to engage in stroke prevention practices compared to those with low knowledge, after controlling for family support and health worker support. Community health centers as primary healthcare facilities should implement various health programs that support efforts of non-communicable diseases preventions, such as health education, community service activities, and medical check-ups.